Bilateral Dislocation of Mandibular Condyles following General Anesthesia—An Overlooked Problem: A Case Report - Toufeeq, Mohd; Kodali, Murali Venkata Rama Mohan; Gunturu, Srikanth; Kumar, Kiran; Surapaneni, Kavya (European Journal of Dentistry, 2019)
Dislocation of mandibular condyles can occur following excessive mouth opening or traumatic injury to the temporomandibular joint. It can also occur during general anesthesia that at times may go un-noticed in the modern-day theater setup. Here, we describe a case of bilateral dislocation of mandibular condyle following orotracheal intubation for general anesthesia. Right condyle was dislocated into temporal fossa.
Keywords: dislocation; condylectomy; temporal fossa